Smart Village Model In Improving Service Quality - Amal, Muhammad Khairul; Meigawati, Dine; Sudarma, Ade (International Journal of Law Policy and Governance, 2022)
A smart village concept can be used as a solution to overcome various problems that occur in the administration of village governance. The purpose of this research is to build a smart village system and find out the benefits of this system. The type of research in this research is descriptive qualitative and the data collection method used in this research is interviews and field observations. From interviews and field observations, demographic data and village economic potential were obtained. The result of this research is the establishment of a smart village model system to improve service quality. Several village problems have been resolved by the Berekah village government, namely up-to-date village demographic data, community economic potential, and other types of services. With this smart village application, the community is well served, without having to wait in long and long queues. The novelty of this smart village model is that it is easy for the community to make population files and other services, as well as demographic data and community economic potential that can be developed.